Resource optimization for UAV relay networks based on physical-layer network coding - Junyi YANG; Bo LI; Qinyu ZHANG (Tongxin xuebao, 2021)
To solve the problem of low resource utilization of the traditional two-way communication network with unmanned aerial vehicle (UAV) as relays, a resource optimization algorithm based on physical-layer network coding was proposed.Considering the transmission power constraints of the UAV relay communication network, the maximum speed constraints of the UAV and the synchronization requirements of the physical-layer network coding, a resource allocation model for joint optimization of transmission power and UAV trajectory design was formulated to minimize the system outage probability.By decoupling the original non-convex problem into two sub-problems, an iterative algorithm was proposed to realize the joint implementation of optimal trajectory design and optimal system power distribution based on the Karush-Kuhn-Tucker (KKT) conditions, Lagrangian duality method and subgradient method.Simulation results show that the proposed algorithm can significantly improve the system performance and reduce the possibility of communication interruption.